<span>A=1/2(a+b)h for h.
First, you need to get rid of 1/2, so divide both sides by 1/2.
A/(1/2) = (a + b)h
You can simplify the </span>A/(1/2) by multiplying by the reciprocal of 1/2, so 2/1.
2A = (a + b)h
Now divide both sides by (a+b).
2A/(a+b) = h
(-∞,0) ∪ (0,∞) is your answer, for any other questions please ask!
Honestly I think you are correct, not trying to take your point. :)
Answer is <span>D. y – 2 = 4(x + 1)
</span><span>not an equation of the line going through (3, 6) and (1, –2)?
...............................................</span>